Analisis Kepuasan Pelanggan terhadap Implementasi ISO 9001: 2015 dengan Menggunakan Pendekatan Servqual (Studi Kasus: Institut Teknologi Telkom Purwokerto) - Yudi Syahrullah; Atik Febriani; Bunga Zati Hulwani (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
September 2018 is the deadline for an organization that has implemented an international standard quality management system ISO 9001: 2008 to switch the latest international standard ISO 9001: 2015. Telkom Institute of Technology Purwokerto is one of the organizations that have implemented the international standard ISO 9001: 2015 since early 2017 (Previously ISO 9001: 2008 implementation). The main objectives of the implementation of ISO 9001 are to improve customer satisfaction both external and internal, including students as the main user of the service organization as an external customer. Therefore, this organization needs to measure the level of student satisfaction with services provided by Telkom Institute of Technology Purwokerto after the organization is implementing ISO 9001: 2015. Data were collected using the questionnaire method consists of 24 questions that designed and analyzed by the SERVQUAL approach. Validity and reliability testing were done by using SPSS software and the measurement result of 24 question items stated Valid and Reliable. From the preliminary research, it was found that the institution should introduce ISO 9001: 2015 to the students at Telkom Institute of Technology Purwokerto. Using the SERVQUAL approach and analyzing GAP 5, comparing the expectations and perceptions of customers (students), the result is that organizations need to improve the speed of the service (academic/student affairs/staff) to students (GAP Value 1.11). In addition, institutions also need to increase the attention of students (GPA Value 1.06). Several efforts have been made with the construction of facilities such as a lecture building that continues to be implemented as well as changes in organizational structure to improve the quality of academic and non-academic services to students.